Discrete Heaped Model of Tobacco Strips Drying and Characteristics Analysis of Heat and Mass Transfer - Qike Wei; Lihua Wang; Wei Jiang; Huaiyu Wang; Hao Zhang (Energies, 2022)
To accurately study the drying characteristics of tobacco strips in the process of redrying, a discrete heaped physical model of tobacco strips is built. Based on this model, a convective drying multiphase porous media model of the heaped tobacco strips is established, which considers the binary diffusion and transport of vapor inside and outside the tobacco leaf. The model is solved using COMSOL Multiphysics, and the accuracy of the model is verified by experiments. The changes in hot air velocity, vapor and moisture content, and evaporation rate in heaped tobacco strips with different thicknesses are analyzed. The results show that: it is feasible to study the drying characteristics of tobacco strips in redrying using a discrete heaped model; there were significant differences in water content, evaporation rate, and temperature in different regions of heaped tobacco strips; the increase in heaping thickness will significantly reduce the uniformity of heat and mass transfer of tobacco strips in the process of convection drying. This model can provide a reference for the study of heat and mass transfer in porous media, such as tobacco strips in the heaping state.